Jewish-Christian relations and the sacramentality of God's word - Pirola, Teresa (The Australasian Catholic record, 2020)
This article explores the idea that, just as the Jewish-Christian dialogue today benefits from the historical consciousness of critical biblical scholarship, so might the dialogue further benefit by a stronger engagement with the corporeal consciousness that permeates both Christian and Jewish traditions in relation to Sacred Scripture. That is, the well-attested 'turn toward history' is also a 'turn toward the body'. Attention to the corporeality of God's word enables a deeper reception of Scripture as 'body' and therefore, I argue, enables Christians to recognise more clearly the word of God embodied in the Torah-centred traditions and living presence of the Jewish people today. The catalyst for my enquiry is Pope Benedict XVI's encouragement of a 'deeper understanding of the sacramentality of God's word' in the mystery of revelation.After examining this theme from the perspective of magisterial, theological and rabbinic sources, I consider its implications for Jewish-Christian relations.